An extension of Wood’s model to describe the lactation performance of dairy animals - PRASAD, SHIV; SINGH, RAM KARAN; SINGH, RAJENDRA (The Indian Journal of Animal Sciences, 2014)
A new lactati on model Y1 = A tbe- tct + d) which is an extension of Wood’s model (Y1 = A tb e-ct) is proposed. The curve has its muximun at rime t = b+âˆ‘-b2 + 4cd)/2c. Wood’s model, Morant and Gnanasakthy model, Mitscherlich x Exponential model and proposed model were fitted to the average weekly milk yields of crossbred cows. The errors generated by the proposed and Mitscherlich x Exponential models followed first order autocorrelation scheme, whereas, the errors generated by the Morant and Gnanasakthy and Wood models followed second and third order autocorrelation scheme respectively. The proposed and Mitscherlich x Exponential odels showed better performance than the Wood and Morant and Gnanasakthy models in deseribing the lactation curve and provided autocorrelated errors of first order only.